Hormone-Producing Potential of Cryopreserved Organotypic Culture of Thyroid Gland During Combined Xenotransplantation - Legach, Ye. I.; Bilyavskaya, S. B.; Bozhok, G. A.; Bondarenko, T. P. (Problems of Cryobiology and Cryomedicine, 2007)
There have been studied T4, TSH, albumin, cholesterol and glucose in blood plasma of thyroidectomized rats with the transplants of cryopreserved organotypic culture of thyroid gland (COCTG) of newborn piglets grafted in combination with the tissue of adrenal glands. It has been shown that co-graft of native fragments of thyroid gland with ones of adrenal glands as well as mono-grafts of native and re-cultured COCTG to the 30th day were capable of subcompensating hypothyroid state in rats.